Konsep Fitrah Manusia Dan Implikasinya Dalam Dunia Pendidikan - Ninda Hamidy, Birru; Komarudin Sassi (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
Human beings are created with an innate disposition (fitrah), a pure and upright potential instilled by Allah from the moment of creation. This study aims to explore the concept of human fitrah in the Qur’an through both analytical (tafsir tahlili) and thematic (tafsir maudhu’i) approaches, and to examine its implications for the design and direction of Islamic education in the contemporary era. Using a literature review method, this research analyzes relevant Qur'anic verses and draws upon classical and contemporary tafsir sources. The findings reveal that human fitrah is not merely a theological concept but serves as an ontological foundation for the development of a holistic educational system. The novelty of this study lies in its conceptual integration of Qur’anic exegesis into educational practice, particularly in designing curricula, pedagogical methods, and learning environments that preserve and nurture the child’s innate disposition from an early age. Through this approach, Islamic education can be oriented toward realizing the values of din al-Islam as al-Din al-Haqq, al-Din al-Qayyim, and al-Din al-Hanif, with amar ma’ruf nahi munkar as the core axis of character development.